2009
DOI: 10.1007/s11469-009-9255-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Issues for Aboriginal Mothers with Substance Use Problems and Their Children

Abstract: In many cultures, approximately one third of people with drug dependence are women of childbearing age. Substance use among pregnant and parenting women is a major public health concern. Aboriginal people have some of the highest rates of substance abuse in Canada, increasing concern for detrimental health impacts, including those for women and their children. For many women, substance abuse offers a means of coping with trauma, such as childhood abuse, partner violence, and, for Aboriginal women, the intergen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 58 publications
(66 reference statements)
1
41
0
Order By: Relevance
“…Related, scholars have reported that Indigenous people's cultural identity is important to their well-being (Berry 1999;Kirmayer et al, 2003;Mohatt et al, 2008;Smillie-Adjarkwa, 2009). This was highlighted most recently in a Canadian study of the healing journeys of First Nations, Inuit, and Métis women recovering from illicit drug abuse (Niccols et al, 2010). These findings support the literature that has identified culture as a key determinant of health and well-being for Aboriginal peoples (Newbold, 1998;Reading, n.d.).…”
Section: Overview Of Relevant Literaturesupporting
confidence: 73%
“…Related, scholars have reported that Indigenous people's cultural identity is important to their well-being (Berry 1999;Kirmayer et al, 2003;Mohatt et al, 2008;Smillie-Adjarkwa, 2009). This was highlighted most recently in a Canadian study of the healing journeys of First Nations, Inuit, and Métis women recovering from illicit drug abuse (Niccols et al, 2010). These findings support the literature that has identified culture as a key determinant of health and well-being for Aboriginal peoples (Newbold, 1998;Reading, n.d.).…”
Section: Overview Of Relevant Literaturesupporting
confidence: 73%
“…In many cultures, approximately one third of people with drug dependence are women of childbearing age [1], and in the USA, five percent of pregnant women reported the use of an illicit drug during pregnancy [2]. In Alberta, the reported prevalence of substance use by pregnant women was 30% for tobacco, 25% for alcohol, and 15% for illicit drugs [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately one third of people with AOD dependence are women of child-bearing age (Niccols, Dell, & Clarke, 2010). Poole (2007) found that many women identify substance use as a way to cope with gender-based abuse and trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous barriers to preventive health care exist for AOD using women, (Burns et al, 2011;Milligan et al, 2002;Niccols et al, 2010;Roberts & Pies, 2011;Rots-de Vries, van de Goor, Stronks, & Garretsen, 2011); these include difficulties accessing services, poverty, coexisting mental illness, guilt, denial or embarrassment regarding their AOD addiction, fear of discomfort or indignity (Chen, Hung, Duffy, Yen & Chen, 2011) and a history of sexual trauma (Taylor, 2011). Pregnancy is known to be a time when women who would otherwise not have access to or make contact with health services do engage with care providers (Higgins, Clough, Frank & Wallerstedt, 1995); antenatal care interactions with AOD addicted women are therefore an ideal time to offer women the Pap smear test, however often, the offer of a Pap smear is missed because of a lack of health practitioners' knowledge or skills (Bayer, Nussbaum, Cabrera, & Paz-Soldan, 2011: Guvenc, Akyuz & Yenen, 2013.…”
Section: Introductionmentioning
confidence: 99%